Preparation of Mixed Oil Pickling Using Capsicum, Green Chilli and Carrot - Molla, MM; Nasrin, TAA; Hossain, M Alamgir (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The study was conducted at Post Harvest Technology Section, HRC, BARI, Gazipur during 2006-2007 to find out a suitable formulation for preparation of mixed oil pickling using capsicum, green chilli and carrot. Three types of mixed oil pickling formulation viz. mature capsicum + green chilli + paste carrots (T1), ripen capsicum + green chilli + paste carrots (T2) and immature capsicum + green chilli + paste carrots (T3) were prepared using varying proportions of capsicum, green chilli and paste carrots. The prepared mixed oil pickles were packed in glass bottle with lug cap. The fresh ingredients and stored pickles were analyzed for nutritional composition. Among the formulation mature capsicum + green chilli + paste carrots (T1) performed the best according to the taste testing panel using sensory attributes comprised colour, flavour, consistency and overall acceptability along with 9-point hedonic scale. Recorded data were analyzed statistically. After 120 days storage periods the nutritional content found little deviation from the fresh ingredients of mentioned formulation. Therefore, it is recommended for prepare mixed oil pickling mature capsicum + green chilli + paste carrots (T1) which may be stored up to 120 days. Key words: Pickling, Vitamin-C, Pro-vitamin-A and storage studies. DOI = 10.3329/jard.v5i1.1458 J Agric Rural Dev 5(1&2), 52-57, June 2007